Overcoming Catabola in the Life of a Specialist of Socionomic Sphere - Hladkova, Valentyna; Pozharskyi, Sviatoslav (Pedagogical Discourse, 2015)
The article analyzes the essence of professional activity of representatives of socionomic sphere. Based on the analysis of studies of philosophers, educators, psychologists, the topicality of the article and its purpose have been formulated – to reveal the essence of catabola in vital activity of the specialist of socionomic sphere and to identify the ways to overcome it. For understanding the directions of development of a mature person the models have been allocated (optimistic, critical, catastrophic crisis, tragic) that characterize the five steps (ways) of its development (velvet, critical, catastrophic, crisis, tragic). The concepts of «acme» and «kata», interdependence and differences between them have been examined. The importance of using modern scientific research in the field of synergistic acmeology for personal and professional self-realization of such specialists has been accentuated. For the analysis and choice of the trajectory of professional development and self-improvement of the worker of socionomic sphere 5 models of this process have been offered: calm, fresh breeze, gusty winds, tailwind, storm. For effective self-improvement and further self-development of the workers of socionomic profile, for successful overcoming by them of catabola in their vital activity, establishment of the service of acmesinergetics guaranteeing of personal and professional development has been proposed.